Factors Affecting Whistleblowing Intention (Studies at Universities in Bali) - Ni Wayan Trisna Kusumayanti; Dewa Gede Wirama; I.G.A.M. Asri Dwija Putri; Komang Ayu Krisnadewi (Budapest International Research and Critics University, 2022)
Fraud is one of the actions that can harm an organization. Therefore, it is important to pay attention to efforts to prevent fraud, one of which is the existence of a whistleblowing system. This study aims to obtain empirical evidence regarding the effect ofproviding financial rewards, personal costs, anonymous reporting channels, and the level of seriousness of fraud on the intentions of the finance department employees to carry out whistleblowing. This research was conducted at universities in the province of Bali. Determination of the sample in this study using purposive sampling. The total sample used is 213 samples. Analysis of the data used is multiple linear regression analysis. The results of this study indicate that financial rewards have a positive effect on whistleblowing intentions. Personal cost has no effect on whistleblowing intention. Anonymous reporting channels have a positive effect on whistleblowing intentions. The level of seriousness of fraud has a positive effect on whistleblowing intentions. The results of this study can be used to optimize whistleblowing intentions. This can be done by optimizing the financial rewards given to employees so that they can meet the needs of employees and will create a strong intention to do whistleblowing.